Seven girls gone ebook - Brennan, Allison (Quinn & Costa, 2023)
"Set among Louisiana's swamps and brooding atmosphere, 'Seven Girls Gone' is a complex mystery whose characters are as intriguing as the storyline." —The Denver Post When nobody will talk and corruption runs deep, turning to outsiders is the only way to make sure women stop disappearing... For three years, women have been disappearing—and eventually turning up dead in the small bayou town of St. Augustine, Louisiana. Police detective Beau Hebert is the only one who seems to care, but with every witness quickly silenced and a corrupt police department set on keeping the cases unsolved, Beau's investigation stalls at every turn. With nobody else to trust, Beau calls in a favor from his friend on the FBI's Mobile Response Team. While LAPD detective Kara Quinn works undercover to dig into the women's murders and team leader Matt Costa officially investigates the in-custody death of a witness, Beau might finally have a chance at solving the case. But in a town where everyone knows everyone, talking gets you killed and secrets stay buried, it's going to take the entire team working around the clock to unravel the truth. Especially when they discover that the deep-seated corruption and the deadly drug-trafficking ring at the center of it all extends far beyond the small-town borders. Look for the next book in Allison Brennan's Quinn & Costa series, THE MISSING WITNESS, now available to order! A Quinn & Costa Thriller Book 1: The Third to Die Book 2: Tell No Lies Book 3: The Wrong Victim Book 4: Seven Girls Gone Book 5: The Missing Witness